Validation of the combination Tectaria pentagonalis (Tectariaceae) - Dong, Shi-Yong (Phytotaxa, 2021)
During the course of sorting out the species of Tectaria Cavanilles (1799: 115, Tectariaceae) in Indochina, I noticed that Tectaria pentagonalis (Phan 2001: 1024) has not validly published. Tectaria pentagonalis seems to be an inadvertent combination, because Phan (2001) did not provide authorship of T. pentagonalis when he made such a combination. The basionym of T. pentagonalis was cited by Phan (2001) in the form “Leptochilus pentagonalis Bonap., 1918”. This citation, according to Art. 41.5 of the International Code of Nomenclature (Turland et al. 2017), does not constitute a full and direct reference to the basionym, because the information of the basionym’s place of valid publication is missing. Thus, T. pentagonalis is justified as invalidly published. So far as I know, the invalidly published Tectaria pentagonalis was also used by Phan (2010) in his another publication and now is adopted in several online resources, such as GBIF (https://www.gbif.org/), Wikipedia (https://es.wikipedia.org/wiki/Tectaria), and “Taxonomic Revision of Fern Genus Tectaria Cav. (Tectariaceae) in Thailand” (http://tectaria.myspecies.info/tectaria/tectaria-pentagonalis). For the purpose of legitimately applying T. pentagonalis in nomenclature, here I validly publish this combination and conveniently designate a lectotype for this species.